A study on the specialization of skills between the left hemisphere and the right hemisphere of the brain - Signar, Lelanie Bacoy (1999)
The specialization of skills between the left hemisphere and the right hemisphere of the brain was studied. There were thirty purposively chosen respondents of the study. Fifteen of whom are right-handed and another fifteen who are left-handed. They were grouped together according to their right-handedness or left-handedness. By the use of a two T-tests, the researcher tested the significance of the two null hypothesis that not all right-handed are skilled in verbal task and mathematical computation and not all left-handed are skilled in spatial difference and in identifying facial expressions of emotions. The findings of this study proved the constructed null hypothesis of no significant difference between the specialization of skills of the left-handed and the right-handed. The capacity or tendency to have a highly developed spatial and pattern sense and in verbal and analytical computation has no connections for being left-handed or right-handed.